Potentiometric study of equilibrium constants of a novel triazine-thione derivative and its stability constants with Hg2+, Cu2+, Ni2+, Pb2+, and Zn2+ metal ions in ethanol and water mixed - Polat, Fatih; Atabey, Hasan; Sari, Hayati; Cukurovali, Alaaddin (Tubitak Scientific & Technological Research Council Turkey, 2013)
The deprotonation constants of 5-hydroxy-5,6-di-pyridin-2-yl-4,5-dihydro-2H-[1,2,4] triazine-3-thione (HPT) and the stability constants of its Hg2+, Ni2+, Cu2+, Pb2+, and Zn2+ ion complexes were studied in 20% ethanol and water mixed at 25 +/- 0.1 degrees C and ionic strength (I) of 0.1 M supported by NaCl. Four pK(a) values of HPT were determined: 3.58, 6.30, 9.23, and 9.69. In various pH conditions, the different complex forms were formulated as ML, MHL, MH2L, MH3L, MH4L, and MH-2L between Hg2+, Ni2+, Cu2+, Pb2+, and Zn2+ ions and HPT. According to the potentiometric and spectrophotometric results, the HPT and Hg2+ combination formed a selective and highly stable complex at pH 7.
Keywords: Potentiometry; triazine-thione; equilibrium constants; proton affinity